2018
DOI: 10.1007/s11764-017-0670-8
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptance evaluation of ACESO: a Web-based breast cancer survivorship tool

Abstract: Using a personal decision support-based tool can serve as a training tool and resource, providing these patients with pertinent information about the various aspects of their long-term health, while educating them about any related side effects and symptoms. It is hoped that making such tools more accessible could help in engaging survivors to play an active role in managing their health and encourage shared decision-making with their providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Upon consultation with breast cancer oncologists, survivors, and a nurse, we have developed and refined the online survivorship care plan, ACESO (Figure 1), and subsequently completed an initial usability assessment to identify any issues. In prior usability and acceptance evaluations, survivors indicated high levels of acceptance and interest in the online survivorship plan [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon consultation with breast cancer oncologists, survivors, and a nurse, we have developed and refined the online survivorship care plan, ACESO (Figure 1), and subsequently completed an initial usability assessment to identify any issues. In prior usability and acceptance evaluations, survivors indicated high levels of acceptance and interest in the online survivorship plan [14].…”
Section: Resultsmentioning
confidence: 99%
“…Lack of time or interest on the part of prospective participants will be a potential barrier to recruitment. To ensure robust recruitment, we will adopt recruitment procedures previously shown to be successful in our pilot [14] and in other studies [56,57]. In addition, the recruitment window will last a full year to allow for adequate recruitment time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26] Survivors as well as their caregivers also report positive attitudes and willingness towards the use of online health information and tools for survivorship support. 25,[27][28][29] mHealth apps can play a key role in filling this gap by providing patients a dynamic platform to continually monitor and track symptoms over time; interact with peer survivors for support and discussion on survivorship topics; provide resources for caregivers; receive reminders for medication or follow-up; and educate themselves on the self-management of survivorship related health concerns at the relevant times. Guided by the Chronic Care Model 26 for patients living with cancer as a chronic illness; and descriptions of mHealth app functionalities from prior reviews, 30,31 we identified six mHealth based basic self-management features (Figure 1…”
Section: Introductionmentioning
confidence: 99%